2017
DOI: 10.1080/00268976.2017.1302610
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated coupled cluster: a heuristic polynomial similarity transformation incorporating spin symmetry projection into traditional coupled cluster theory

Abstract: In electronic structure theory, restricted single-reference coupled cluster (CC) captures weak correlation but fails catastrophically under strong correlation. Spinprojected unrestricted Hartree-Fock (SUHF), on the other hand, misses weak correlation but captures a large portion of strong correlation. The theoretical description of many important processes, e.g. molecular dissociation, requires a method capable of accurately capturing both weak-and strong correlation simultaneously, and would likely benefit fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…While such models are solvable by U (1)-breaking BCS mean-field theory in the thermodynamic limit, it is important to obtain an accurate description for mediumsize systems as well 46,108,109 . In fact, it has been shown that the Richardson-Gaudin equations are equivalent to the BCS mean-field equations for thermodynamically large systems, and as such the BCS wave function and the Bethe ansatz wave function coincide in this limit 53 .…”
Section: B Perturbing the Richardson Modelmentioning
confidence: 99%
“…While such models are solvable by U (1)-breaking BCS mean-field theory in the thermodynamic limit, it is important to obtain an accurate description for mediumsize systems as well 46,108,109 . In fact, it has been shown that the Richardson-Gaudin equations are equivalent to the BCS mean-field equations for thermodynamically large systems, and as such the BCS wave function and the Bethe ansatz wave function coincide in this limit 53 .…”
Section: B Perturbing the Richardson Modelmentioning
confidence: 99%
“…However, in the case of projected CC wave functions, there are two possibilities that differ in the way of generating the broken symmetry CCSD wave function, namely by variational approach or similarity transformation . But, the most encouraging seems to be the possibilities of the projected CCSD method.…”
Section: Resultsmentioning
confidence: 99%
“…17 we have explored the simple wave function ansatz |Ψ = exp(T )|PHF in a variational framework as a precursor to more computationally useful approaches which use the correlator exp(T ) to define a similarity-transformed Hamiltonian as in traditional coupled cluster theory. Our work on attenuated coupled cluster [26] follows similar ideas. Much earlier work explored writing the PHF wave function as an exponential of higher-order cluster operators (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…where both contain only double excitation operators which, like the SGHF excitation operators, are parameterized in terms of the Thouless transformation taking RHF to the broken-symmetry determinant. This observation for number and S 2 spin projection forms the basis for our work on what we call attenuated coupled cluster, [26] in which we add the SUHF or PBCS polynomial to the coupled cluster exponential, thereby substantially mitigating the failures of traditional coupled cluster theory in the stongly correlated limit. Both the SUHF and the PBCS polynomials are examples of (univariate) hypergeometric functions, as indeed is the exponential of coupled cluster theory; the SGHF polynomial is a multivariate generalization.…”
Section: The Sghf Wave Functionmentioning
confidence: 97%